Analysis of apps used by teachers with autism students in early childhood in Spain. - Trujillo Torres, Juan Manuel; Fernández Montoro, Dulce; Benítez-Márquez, María Dolores; Fernández Fernández, Carmen Rocío (Universidad de Sevilla, 2025)
The importance of the benefits obtained from the use of new technologies in the teaching-learning process is agreed-upon by most of the authors who have published about technologies, education, and autism. Likewise, in Spain, there are very little empirical studies on teachers in the early childhood stage with autistic children (3 to 6 years old). This justifies the present cross-sectional study, which includes the participation of 251 active teachers residing in Andalusia (Spain). The aim of the study is to provide knowledge on a specific technology (apps) used by the professionals in the context described. Among other objectives, in first place, the skills that need to be developed by the autistic students, through the use of 23 Spanish-language apps, are classified, at the same time that the characteristics of the apps are summarized. Additionally, an analysis is performed of the significant differences in the number of different apps used by each teacher with respect to gender, school location (rural-urban), age, years of teaching experience, and years of teaching autistic children. In third place, the linear correlation was performed between the number of different apps used by each teacher and age. Among the most notable conclusions, with respect to skills, the apps that developed the needs to be improved related with communication and socio-emotional aspects were the most valued, while the ones related to behavior were least valued. With respect to the summary of their characteristics, all the apps used in Spain were free, and both Spain and the USA were notable for the creation of the apps selected. Lastly, the number of different apps used by the teachers and age had a scarce negative relation.
Análisis de apps utilizadas por profesores con alumnado autista en la etapa infantil en España.
Keywords: Tecnología educativa; Educación infantil; Profesores de educación infantil; Niños con trastornos del espectro autista - Educación; Applications-apps; Autism (ASD); Information and Communication Technologies (ICT); Early childhood education; Teacher